Community music therapy - Pavlicevic, Mercedes; Ansdell, Gary. (London ; New York : Jessica Kingsley Publishers, 2004)
"Music therapists from around the world working in conventional and unconventional settings have offered their contributions to this exciting new book, presenting spirited discussion and practical examples of the ways music therapy can reflect and encourage social change. From working with traumatized refugees in Berlin, care-workers and HIV/AIDS orphans in South Africa, to adults with neurological disabilities in south-east England and children in paediatric hospitals in Norway, the contributors present their global perspectives on finding new ways forward in music therapy. Reflecting on traditional approaches in addition to these newer practices, the writers offer fresh perceptions on their identity and role as music therapists, their assumptions and attitudes about how music, people and context interact, the sites and boundaries to their work, and the new possibilities for music therapy in the 21st century. As the first book on the emerging area of Community Music Therapy, this book should be an essential and exciting read for music therapists, specialists and community musicians."--Publisher's website.
Foreword: Reclaiming Music -- Introduction: 'The Ripple Effect' -- PART I: New Name, Old Game? -- 1. Learning from Thembalethu: Towards Responsive and Responsible Practice in Community Music Therapy -- 2. From Therapy to Community: Making Music in Neurological Rehabilitation -- PART II: What has Theory got to do with it? -- 3. Rethinking Music and Community: Theoretical Perspectives in Support of Community Music Therapy -- 4. Community Music Therapy: Culture, Care and Welfare -- 5. What can the Social Psychology of Music offer Community Music Therapy? -- PART III: Is Community Music Therapy a Challenge to the Consensus Model? -- 6. Whatever Next? Community Music Therapy for the Institution! -- 7. A Pied Piper among White Coats and Infusion Pumps: Community Music Therapy in a Paediatric Hospital Setting -- PART IV: But is it Music Therapy? -- 8. A Dream Wedding: From Community Music to Music Therapy with a Community -- 9. Conversations on Creating Community: Performance as Music Therapy in New York City -- 10. Playing Politics: Community Music Therapy and the Therapeutic Redistribution of Musical Capital for Mental Health -- PART V: What has Culture got to do with it? -- 11. Promoting Integration and Socio-cultural Change: Community Music Therapy with Traumatised Refugees in Berlin -- 12. Community Music Therapy and the Challenge of Multiculturalism -- PART VI: What has Context got to do with it? -- 13. Music, Space and Health: The Story of MusicSpace -- 14. Narratives in a New Key: Transformational Contexts in Music Therapy.
Includes bibliographical references and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Music therapy; Music -- Social aspects; Music Therapy; Musicothérapie.; Musique -- Aspect social; Creative Therapy (Eg Art, Music, Drama); MEDICAL -- Allied Health Services -- Occupational Therapy; Music -- Social aspects; Music therapy